An investigation of the anti-oxidant, antimicrobial and wound healing properties of whole leave juice and gelpowders of Aloe ferox and Aloe vera - Cromarty, Allan Duncan (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2014.